The Effect of Web-based and Simulation-based Education on Midwifery Students' Self-Confidence in Postpartum Hemorrhage Management - Masoumeh Kordi; Farzaneh Rashidi Fakari; Talaat Khadivzadeh; Seyed Reza Mazloum; Farideh Akhlaghi; Mahmoud Tara (Mashhad University of Medical Sciences, 2015)
Background & aim:  Self-confidence, as one of the key elements of clinical competence, plays an important role in one's actions and behaviours. Selection of proper instructional methods influences students' self-confidence. Therefore, this study aimed to compare the effects of web-based training and educational simulation on midwifery students' self-confidence in postpartum hemorrhage management. Methods: This experimental study was conducted on 44 midwifery students of Mashhad School of Nursing and Midwifery, Mashhad, Iran, in 2013. The subjects were selected via convenience sampling. The web-based group was trained at the clinical skill laboratory of School of Nursing and Midwifery; both groups were taught the same educational content. Data were collected using a demographic questionnaire, visual analogue scale to evaluate students' self-assessment of their ability to manage postpartum hemorrhage and C-scale to measure students' self-confidence Descriptive analysis, independent t-test, paired t-test, and two-way ANOVA were performed, using SPSS version 11.5. Results: Both groups showed a significant increase in self-confidence in postpartum hemorrhage management one month after the training (P=0.003 and P=0.030 in web-based and simulation groups, respectively). No significant difference was found between the two groups in terms of self-confidence in postpartum hemorrhage management. Conclusion: Since the two groups showed no significance difference in self-confidence, web-based education, which is a more accessible method, could be applied as an alternative to the conventional method of simulation.